17‐level inverter with low component count for open‐end induction motor drives. Issue 5 (1st March 2018) - Kshirsagar, Abhijit; Kaarthik, R. Sudharshan; Rahul, Arun; Gopakumar, K.; Umanand, Loganathan; Biswas, Sujit K.; Cecati, Carlo
Abstract : This study presents a 17‐level inverter‐based induction motor drive for high‐resolution multilevel voltage space‐vector (SV) generation. The proposed topology consists of a three‐level inverter and a seven‐level inverter connected to an open‐end winding induction machine. The two inverters are powered by two unequal DC supplies, resulting in a low component count, with just 12 switches and three floating capacitors per phase. The voltage SVs applied by the two inverters are chosen to eliminate circulating power flow and prevent DC bus overcharging. In addition, the switching states of both inverters are chosen in order to keep voltages of all floating capacitors well‐controlled. Since the capacitors voltages are controlled using the phase currents, additional pre‐charging circuitry is not required. A modulation scheme using level‐shifted carriers has also been developed, which can be used with both V/f control and d–q control. The high‐voltage inverter has a low effective switching frequency and the low‐voltage inverter has a high effective switching frequency, reducing the switching loss. The included results of steady‐state and transient testing of an experimental prototype demonstrate that the proposed scheme is suited for industrial drives and traction applications.